Ferrerol overcomes the invasiveness of lung squamous cell carcinoma cells by regulating the expression of inducers of Epithelial Mesenchymal Transition. (November 2017) - Li, Bin; Chen, Peng; Wang, Jie-Hua; Li, Li; Gong, Jin-Lan; Yao, Hui
Abstract: In recent years Epithelial Mesenchymal Transition (EMT) has been proposed as a mechanism indispensable to acquisition of metastatic properties by tumor cells. In this study we tested the ability of Ferrerol, a Chinese herb-derived compound to ablate the EMT in human lung squamous cell carcinoma cells. Human lung squamous cell carcinoma cells, Calu-1 were treated with various concentrations of Ferrerol for 24 h to examine its effect on their viability by the MTT assay. Only those concentrations which showed least effect on the viability of Calu-1 cells were further used to evaluate the expression of epithelial and mesenchymal markers by western blotting. Furthermore the effect of such concentrations on the migration and invasion of Calu-1 cells was determined by wound healing and transwell invasion assays respectively. The results demonstrated that Ferrerol treatment led to the downregulation of Slug and Zeb-1, transcriptional regulators of EMT with the concomitant increase and decrease in the expression of E-cadherin and vimentin respectively. These data were further supported by migration and invasion assays which demonstrated that Ferrerol treatment caused inhibited the migration and invasion of Calu-1 lung squamous cell carcinoma cells. Taken together, our results indicate that Ferrerol suppresses lung squamous cell carcinoma cell metastatic potential by modulating the expression of EMT proteins. Highlights: Ferrerol treatment inhibits the migration and invasion of Calu-1 lung squamous cell carcinoma cells. Ferrerol suppresses lung squamous cell carcinoma cell metastatic potential by modulating the expression of EMT proteins. Data of study represent that Ferrerol could be use clinically for the management of lung cancer.